Knowledge and attitudinal survey of drug promotional literature among second year undergraduate students: a questionnaire based study - Agrawal, Ratna; Jaiswal, Mahendra Kumar; Sharma, Sanat Kumar; Sharma, Raj (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Promotion of drugs has been increased enormously with the advancement of technology and use of internet and media etc. Pharmaceutical manufacturers spend vast amount of money on promotion usually through medical representatives by providing printed advertisements. But, it has been seen that these printed advertisements are not up to the mark usually, they either overemphasize the efficacy or hide the safety profile for the sake of company’s profit. All these promotional activities influence the prescribing pattern of doctors. So, the present study has been conducted to assess the knowledge and attitude of second year undergraduate students about promotional literature and to train them accordingly for improving the prescribing behaviour. Methods: A questionnaire based study containing 9 questions was conducted in 110 second year undergraduate students after taking informed consent. Statistical analysis was done by using descriptive statistics by graph pad prism version 6.01. Results: Among respondents 60 (61.2%) were males and rest 38 (38.8%) were females. 50 (51%) of the respondents have chosen Indian pharmacopoeia as a trusted source of information followed by others. Most common factor affecting the prescribing attitude was reported as updates from clinical trials 49 (50%) followed by prescriber’s knowledge. Most important intervention taken to stop misleading drug promotional activities has been reported as formulation of strict regulation by the health care authorities against any misleading promotion. Conclusions: Promotional activities by manufacturers influence the attitude and prescribing pattern of doctors. So, it is important to teach the students about their rational use by critically analysing it.